Self-monitoring of intraocular pressure using Icare HOME tonometry in clinical practice - Cvenkel B (Dove Medical Press, 2019)
Barbara Cvenkel,1,2 Makedonka Atanasovska Velkovska11Department of Ophthalmology, University Medical Centre Ljubljana, Ljubljana, Slovenia; 2Medical Faculty, University of Ljubljana, Ljubljana, SloveniaPurpose: To determine the value of self-monitoring of diurnal intraocular pressure (IOP) by Icare Home rebound tonometer in patients with glaucoma and ocular hypertension.Methods: Patients with open-angle glaucoma or ocular hypertension, controlled IOP at office visits, and at least 3 years of follow-up in the glaucoma clinic were included. Progression of glaucoma was based on medical records and defined by documented structural and/or visual field change. Patients were trained to correctly perform self-tonometry and instructed to measure diurnal IOP in a home setting for 3 days. IOP characteristics (mean, peak IOP, fluctuation of IOP as range, and SD of IOP) were documented and compared between the progressive and stable eyes.Results: Ninety-four patients (50 females) with a mean (SD) age of 57.1 (14.7) years were included. Among the 94 eyes from 94 subjects, 72 (76.6%) eyes had primary open-angle glaucoma, ten (10.6%) had pigmentary glaucoma, four (4.3%) had exfoliative glaucoma, and eight (8.5%) eyes had ocular hypertension. Thirty-six eyes showed progression and 58 eyes were stable. Patients with progression were older than those with stable disease (mean (SD) 65.8 (8.4) years vs 51.7 (15.3) years, P<0.001). The progression group had higher average IOP (mean (SD) 15.8 (4.0) mmHg vs 13.3 (3.7) mmHg, P=0.002), peak IOP (mean (SD) 21.8 (5.8) mmHg vs 18.6 (4.8) mmHg, P=0.01), and greater IOP fluctuation range (mean (SD) 11.6 (4.8) vs 9.1 (3.5) mmHg, P=0.011) compared to non-progression group.Conclusion: Self-monitoring of IOP using Icare Home tonometry provides more complete data on variability of IOP to assist in the management of glaucoma.Keywords: glaucoma, intraocular pressure, progression, self-tonometry